Position deceptive tracking controller and parameters analysis via error characteristics for unmanned aerial vehicle. (14th February 2019) - Guo, Yan; Wu, Meiping; Tang, Kanghua; Tie, Junbo; Zhang, Jingyu
Covert Global Navigation Satellite System spoofer, called position deceptive tracking controller for unmanned aerial vehicle, is studied via analyzing the error characteristics in this article. Specifically, the following topics are discussed: (1) design the position deceptive tracking controller to make unmanned aerial vehicle deviate from the original path and follow up the spoofed new path point by point, and (2) analyze the related parameters by exploring the characteristics of the initial estimated state errors. Simulation results show the designed controller can realize the position offset of unmanned aerial vehicle unknowingly. What's more, it can eliminate the initial state errors by selecting appropriate parameters.